2019
DOI: 10.1037/dev0000697
|View full text |Cite
|
Sign up to set email alerts
|

Breaking down gesture and action in mental rotation: Understanding the components of movement that promote learning.

Abstract: Past research has shown that children's mental rotation skills are malleable and can be improved through action experience-physically rotating objects-or gesture experience-showing how objects could rotate (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 47 publications
(69 reference statements)
1
11
0
19
Order By: Relevance
“…Although such training was sufficient to raise children’s mental rotation scores, it might not have been extensive or detailed enough to show transfer to mathematics performance. Consistent with this possibility, a recent study found that 5-year-olds’ mental rotation ability benefited more from training that involved gesturing the rotation than from training that involved rotating an image on a touchscreen (Wakefield et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Although such training was sufficient to raise children’s mental rotation scores, it might not have been extensive or detailed enough to show transfer to mathematics performance. Consistent with this possibility, a recent study found that 5-year-olds’ mental rotation ability benefited more from training that involved gesturing the rotation than from training that involved rotating an image on a touchscreen (Wakefield et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…In older children and adults, spatial skills predict Science, Technology, Engineering, and Mathematics achievement and career paths, even when controlling for numerical and verbal abilities (25,(72)(73)(74)(75)(76). Although there are socioeconomic disparities in foundational spatial skills (35,39), spatial thinking can be improved with instruction and practice (67,77,78). Moreover, training children's spatial thinking improves their numerical math skills (66,67).…”
Section: Foundational Mathematical Skillsmentioning
confidence: 99%
“…These data also lay a foundation for developmental work on children's use of theory of mind in gestural communication. A substantial literature has explored the impact of gesture on children's learning: When children are instructed to use gestures, they perform better on math problems (Goldin-Meadow et al, 2009;Novack et al, 2014) and mental rotation tasks (Wakefield et al, 2019). Children's spontaneous gestures can also show implicit understanding of a concept, even when explicit verbal answers are incorrect, signalling a transitional state of understanding predictive of future learning (Church & Goldin-Meadow, 1986;Goldin-Meadow & Wagner, 2005;Perry et al, 1988).…”
Section: The Development Of Gestural Communicationmentioning
confidence: 99%